The effects of iron replacement on functional capacity in patients with group 1 and group 4 pulmonary hypertension - ATAŞ, HALİL; KOCAKAYA, DERYA; YILDIZELİ, BEDRETTİN; MUTLU, BÜLENT (My University, 2022)
Objective: Abnormal iron handling complicates pulmonary hypertension and causes functional limitation and poor outcomes. Although preliminary results in group 1 pulmonary hypertension patients support the use of iron replacement, whether this applies to other PH subgroups is not known.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; CARDIAC ve CARDIOVASCULAR SİSTEMLER; Klinik Tıp; Klinik Tıp (MED); CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); Kardiyoloji ve Kardiyovasküler Tıp; Cardiology and Cardiovascular Medicine; Anemia; chronic thromboembolic pulmonary hypertension; ferric carboxymaltose; pulmonary arterial hypertension; pulmonary hypertension; IMPROVES EXERCISE CAPACITY; QUALITY-OF-LIFE; ARTERIAL-HYPERTENSION; DEFICIENCY; THERAPY